SLAVOPHILISM AND WESTERNIZATION IN THE PHILOSOPHICAL PERCEPTION OF M. BERDYAEV - Попков, В. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Different peculiarities of Berdyaev’s approach to the history and the intellectual content of conflict of westerners and Slavophiles are studied in the article. Especially notable is M. Berdyaev’s analysis of power problem.